Testing eddy compensation and eddy saturation in the Southern Ocean - Jones, Daniel C., author; Ito, Takamitsu, advisor; Birner, Thomas, committee member; Lovenduski, Nicole, committee member; Randall, David, committee member; Tavener, Simon, committee member (Colorado State University. Libraries, 2013)
The Southern Ocean (SO) is a unique and dynamic component of the climate system. Due in part to its cold temperatures and large surface area, the SO is an important region for the transfer of heat, momentum, and climatically relevant gases between the atmosphere and the interior ocean. The strong westerly winds above the SO help drive a powerful current (i.e. the Antarctic Circumpolar Current or ACC) that connects Earth's ocean basins in a global overturning circulation. In recent decades, these winds have strengthened and shifted poleward. Despite this change in surface forcing, no clear observational signal of the oceanic density structure's response has yet been detected. The eddy compensation hypothesis posits that changes in the direct wind-driven overturning circulation are balanced by changes in the eddy-induced meridional circulation, effectively rendering SO stratification insensitive to wind stress. The closely related (but not identical) eddy saturation hypothesis suggests that the ACC is also insensitive to increased wind stress, since additional energy ends up in the mesoscale eddy field instead of in the zonal mean circulation. In this work, we examine the viability of the eddy compensation and saturation hypotheses on interannual, decadal, and centennial timescales. Using a combination of theory and idealized numerical simulations, we show that it may take the Southern Ocean many decades to centuries to fully equilibrate with the world ocean following a change in wind stress. As such, it may be difficult to detect changes in isopycnal slope using the few decades of available observational data. We also explore the characteristics of eddy-driven interannual variability and examine how this variability may affect the decadal-scale adjustment of the global ocean. Our results suggest that departures from the eddy compensation regime may be important on decadal and centennial timescales, on which the interaction between regional Southern Ocean circulation and global ocean circulation is significant. As such, we suggest that Southern Ocean overturning circulation is likely to strengthen in response to recent and future climate change, with implications for the global carbon cycle and climate.
Keywords: modeling; wind stress; climate change; eddy compensation; eddy saturation; Southern Ocean